Usage of secret servise files in Germany - Bormann , Gunter (Genocidas ir rezistencija, 2006)
The buildings of the State Security Service in Germany were taken over by human rights activists in autumn 1989. During the initial phase of the peaceful revolution, files were handed over to citizens for safekeeping. In autumn 1989, the Stasi staff tried very hard to destroy the files, days and nights at a stretch. They also had another problem: they did not have the equipment to destroy the files. Then the Stasi staff were surrounded. They started to tear the files into small pieces, piling them into 15,000 rubbish bins. During that transitional period, the State Security Service did not have time to falsify documents, and the Communist Party and its political police were not able to use the information for their own political purposes. In Germany, the files of the State Security Service were preserved. This was the first step leading towards a unique solution – to allow access to the Stasi files.
Keywords: Germany; Stasi; repressive structures; archive; agents